Insights into large landslide mechanisms in tectonically active Agadir, Morocco: The significance of lithological, geomorphological, and soil characteristics - Fatima Machay; Said El Moussaoui; Hajar El Talibi (Scientific African, 2023)
Landslide susceptibility assessment is crucial for land use planning, infrastructure development, and hazard mitigation, particularly in tectonically active regions where lithology and soil characteristics significantly influence slope stability. This study aims to evaluate landslide susceptibility in the Agadir Ida-Ou-Tanane province, a tectonically active area, using a hierarchical multicriteria analysis approach. Eight factors influencing landslide occurrence were considered: lithology, slope, LULC, distance to main faults, hypsometry, drainage density, road density, and aspect. Pairwise comparison matrices and expert opinion were employed to determine the relative importance of these factors. The consistency ratio (CR) was calculated to ensure the reliability of the judgments. The resulting landslide susceptibility map reveals a spatial distribution ranging from very low to very high susceptibility zones. Lithology, mainly clay, and limestone formations, emerged as the most influential factor due to the active tectonic context of the study area. The model was validated using observed landslide locations and the Area Under the Curve (AUC) method, yielding a reasonable validation accuracy. The findings indicate that integrating these factors, with a particular emphasis on lithology and soil characteristics, effectively identifies areas prone to landslides, making the resulting map a valuable tool for land use planning and risk management in the Agadir Ida-Ou-Tanane region. This study contributes to understanding landslide susceptibility in tectonically active areas and provides a practical foundation for future research and decision-making. Regularly monitoring and updating the landslide susceptibility map is necessary to ensure its continued relevance and utility for stakeholders.